2016
DOI: 10.1016/j.neo.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Promote Pancreatic Tumor Growth by Inducing Alternative Polarization of Macrophages

Abstract: Pancreatic cancer is characterized by an extensive desmoplastic stroma, the functional relevance of which is poorly understood. Activated fibroblasts are a prevalent component of the stroma, and traditionally, these cells have been considered as a homogenous population derived from pancreatic stellate cells. In this study, we highlight a previously unappreciated heterogeneity of the fibroblast population within the stroma. In particular, a subset of stromal fibroblasts has characteristics of mesenchymal stem c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 36 publications
(41 reference statements)
2
72
0
3
Order By: Relevance
“…S7A and S7B), suggesting that GM-CSF plays a role in the recruitment and polarization of TAMs in the tumor microenvironment. These results are consistent with a recent report demonstrating a role for CA-MSCs in regulating macrophage polarization (26). …”
Section: Resultssupporting
confidence: 94%
“…S7A and S7B), suggesting that GM-CSF plays a role in the recruitment and polarization of TAMs in the tumor microenvironment. These results are consistent with a recent report demonstrating a role for CA-MSCs in regulating macrophage polarization (26). …”
Section: Resultssupporting
confidence: 94%
“…MSCs have been shown to have tumor‐promoting effects stimulating directly tumor growth . In order to explore whether the lack of TSG‐6 exacerbates this effect, we evaluated tumor growth in xenograft models by subcutaneously implanting two different adenocarcinoma cell lines (A549 lung cancer cell line or colon cancer cell line Caco‐2) in coadministration with MSCs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, mice treated with TSG-6 −/− -MSCs displayed higher levels of IL-6 than those receiving WT-MSCs cells; i.e., consistent with the loss of TSG-6 in MSCs enhancing the release of IL-6 (see above), which could have the effect of amplifying the pro-tumorigenic effects of MSCs in specific tissues. MSCs have been shown to have tumor-promoting effects stimulating directly tumor growth [13,[50][51][52][53][54]. In order to explore whether the lack of TSG-6 exacerbates this effect, we evaluated tumor growth in xenograft models by subcutaneously implanting two different adenocarcinoma cell lines (A549 lung cancer cell line or colon cancer cell line Caco-2) in coadministration with MSCs ( Fig.…”
Section: Tsg-6 −/− -Mscs Conditions the Tumor Microenvironmentmentioning
confidence: 99%
“…Initial studies reported that IL-6 produced by CAFs switched monocyte differentiation programs towards a tumor-promoting M2 lineage[25]. Subsequent in vitro studies of tumor cell-CAF interactions and proteomic profiles of CAFs isolated from tumor models identified numerous pro-inflammatory cytokines such as GM-CSF, CSF-1, CCL2, CCL7, CXCL1, CXCL2, and CXCL8 that are involved in MDSC recruitment and differentiation of macrophages into a pro-tumor M2 phenotype[2628], which is likely due to suppression of M1-promoting pathways. Activated fibroblasts have also been reported to directly regulate myeloid cell maturation.…”
Section: Cafs As Regulators Of Immunosuppressive Myeloid Cellsmentioning
confidence: 99%